Fecal Sludge Management : Diagnostics and Guidelines for Sservice Delivery in Urban Areas - World Bank Group (World Bank, Washington, DC, 2016)
Urban sanitation remains a significant challenge for most low- and middle-income countries. While sanitation coverage has been increasing across both the 48 least developed countries (LDCs) and developing regions as a whole, progress has been relatively slow. In many cities, even where improved on-site facilities are used to contain excreta, the level of quality and access to services for the emptying, conveyance, treatment, and disposal of the resulting fecal sludge is usually limited. These services are collectively called fecal sludge management (FSM) services. FSM services are the focus of this study, within the broader context of urban sanitation and integrated urban water management (IUWM). This document provides a summary of the diagnostic tools developed for assessing FSM services and is based on field work carried out in the five cities of Balikpapan in Indonesia, Dhaka in Bangladesh, Hawassa in Ethiopia, Lima in Peru, and Santa Cruz in Bolivia. It summarizes the tools themselves, lessons learnt about their use, and general policy recommendations.